Review Sistematis: Pengaruh Kondisi Penyimpanan Terhadap Stabilitas Tablet Vitamin C Dan Aspirin - Ramadhany, Arifa Salsabilla; Utami, Marsah Rahmawati; Ramadhani , Dwi Arifa; Lismawan , Gita Novianti (Journal of Pharmaceutical and Sciences, 2025)
This study aims to determine the most optimal storage conditions for maintaining the stability of vitamin C and aspirin tablets by considering key environmental factors such as temperature, humidity, light exposure, and storage duration. The review was conducted using a systematic review approach based on the PRISMA guidelines. Literature searches were performed through three main sources, namely PubMed, ScienceDirect, and Google Scholar, covering publications from 2015 to early 2025. The search through Google Scholar was carried out to complement the findings and minimize publication bias. A total of 14 research articles that met the inclusion criteria were analyzed in depth. The results indicate that vitamin C tablets exhibit the highest stability at low to room temperature (<30°C), under dry conditions with relative humidity below 75% RH, and protected from direct light exposure. In contrast, aspirin tablets show optimal stability at room temperature (around 25°C), under moderate humidity (<60% RH), and when stored in tightly sealed, light-resistant containers. The degradation of vitamin C is primarily driven by oxidation induced by heat, light, and moisture, whereas aspirin undergoes hydrolysis under humid and high-temperature conditions. Therefore, storing both tablets in a cool, dry place away from direct light is the most effective approach to preserve their stability and therapeutic efficacy throughout their shelf life.